2016
DOI: 10.1111/fcp.12194
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane anesthesia induces neither contextual fear memory impairment nor alterations in local population connectivity of medial prefrontal cortex local field potentials networks in aged rats

Abstract: Sevoflurane has been found to increase apoptosis and pathologic markers associated with Alzheimer disease, provoking concern over their potential contribution to postoperative cognitive dysfunction. This study aimed to determine the effects of sevoflurane on contextual fear memory of aged rats and to characterize local population connectivity of local field potentials (LFPs) in medial prefrontal cortex (mPFC) of aged rats during contextual fear memory. Eighteen-month-old male SD rats were implanted with one mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Exposure to anesthesia in the absence of a surgical stress does not reliably impair cognition when younger animals are utilized [72]. When aged animals are employed, there has been conflicting evidence assessing whether anesthesia exposure can lead to cognitive impairment [7376]. The variability in results is likely impacted by heterogeneity in study design, including choice of animal models, age of animals, choice of anesthesia agent, dose, duration of exposure, and the choice of cognitive test and timing of assessment relative to anesthesia exposure.…”
Section: Main Bodymentioning
confidence: 99%
“…Exposure to anesthesia in the absence of a surgical stress does not reliably impair cognition when younger animals are utilized [72]. When aged animals are employed, there has been conflicting evidence assessing whether anesthesia exposure can lead to cognitive impairment [7376]. The variability in results is likely impacted by heterogeneity in study design, including choice of animal models, age of animals, choice of anesthesia agent, dose, duration of exposure, and the choice of cognitive test and timing of assessment relative to anesthesia exposure.…”
Section: Main Bodymentioning
confidence: 99%
“…Sevoflurane is a colorless and volatile liquid anesthetic with a peculiar smell that is used to maintain clinical general anesthesia ( Lu et al, 2010 ; Jiang et al, 2017 ; Yukina et al, 2019 ). Although sevoflurane has numerous advantages, such as universal applicability and safety over other anesthetics, several studies have demonstrated that sevoflurane administration can cause cognitive impairment including postoperative cognitive dysfunction (POCD) and AD ( Lu et al, 2010 ; Xu et al, 2016 ). Certain inhaled anesthetics have been reported to enhance the formation of Aβ plaques and neurofibrillary tangles in animal models ( Xie et al, 2006 ; Ikeda et al, 2007 ; Planel et al, 2007 ; Bianchi et al, 2008 ; Zheng et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…An additional study found that levels of AD biomarkers (tau and Aβ) were increased following surgical procedure, but were unaffected by anesthesia exposure alone [29]. Animal studies find that the anesthetic sevoflurane alone has no effect on contextual fear memory or synaptic plasticity/connectivity in the medial pre-frontal cortex, but in combination with a surgical procedure did impair memory and connectivity [38]. Thus, there are abundant studies both in support and in disagreement with this hypothesis with conflicting evidence across human and animal studies of anesthetics and surgery.…”
Section: Postoperative Cognitive Delirium and Alzheimer's Diseasementioning
confidence: 99%